2021
DOI: 10.33182/ml.v18i6.917
|View full text |Cite
|
Sign up to set email alerts
|

Remittances and subjective well-being: A static versus dynamic panel approach to happiness

Abstract: Using all five waves of the National Income Dynamics Study (NIDS) panel dataset, we examine the effect of domestic remittances on the static and dynamic subjective well-being (SWB) of recipient individuals in South Africa, by using a random effects ordered probit model that accounts for individual heterogeneity. Moreover, we check the robustness of our static model results by making use of an instrumental variable for migrants’ remittances. Two major empirical findings emerge from this paper: firstly, domestic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Also, as international migrants usually change their place of residence from one country to another, they tend to have higher expectations in building a thriving life satisfaction around them and their households. Studies have supported this finding and explained that international migrants usually have higher expectations and are usually seen working towards achieving their dreams of a thriving life satisfaction [ 102 , 103 ]. This exciting finding suggests that migrant status significantly predicts the highest life satisfaction of migrant males and females.…”
Section: Discussionmentioning
confidence: 91%
“…Also, as international migrants usually change their place of residence from one country to another, they tend to have higher expectations in building a thriving life satisfaction around them and their households. Studies have supported this finding and explained that international migrants usually have higher expectations and are usually seen working towards achieving their dreams of a thriving life satisfaction [ 102 , 103 ]. This exciting finding suggests that migrant status significantly predicts the highest life satisfaction of migrant males and females.…”
Section: Discussionmentioning
confidence: 91%
“…Emerging and low-income countries were impacted negatively in the areas of trade, investment and remittances channels (Chipeta 2011). Biyase, Fischer and Pretorius (2021) reported on the importance for remittances for material survival for recipient households as well as the positive impact on these households' subjective well-being. Richter and Patel (2022) furthermore concluded that in Brazil the self-employed (especially largely informal and often racial minority workers) suffered relative more from this worldwide health crisis.…”
Section: Introduction and Rationale For The Studymentioning
confidence: 99%
“…In the study conducted by (Ivlevs, Nikolova & Graham, 2019) using Gallup World Poll data for 2009-2011, it was shown that poorer families with a family member who has migrated abroad report higher levels of well-being. (Biyase, Fisher & Pretorius, 2021) According to the results of the study conducted in South Africa, remittances have a continuous positive impact on the happiness of family members.…”
Section: Introductionmentioning
confidence: 99%